2011
DOI: 10.1097/jto.0b013e3182272294
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Mesothelin, Megakaryocyte Potentiating Factor, and Osteopontin as Markers of Patient Response and Outcome in Mesothelioma

Abstract: SM and MPF levels were more closely associated with disease course than OPN and might prove useful in monitoring patient response in mesothelioma. Baseline OPN levels were an independent negative predictor of survival. These promising results require further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 36 publications
7
75
0
1
Order By: Relevance
“…Regarding response to treatment, in contrast to mesothelin and MPF which decrease shortly after resection, osteopontin increases [39]. This probably highlights the effect of wound healing and tissue remodelling on osteopontin levels.…”
Section: Osteopontinmentioning
confidence: 92%
See 3 more Smart Citations
“…Regarding response to treatment, in contrast to mesothelin and MPF which decrease shortly after resection, osteopontin increases [39]. This probably highlights the effect of wound healing and tissue remodelling on osteopontin levels.…”
Section: Osteopontinmentioning
confidence: 92%
“…Mesothelin measurement may be helpful to overcome this problem. If confirmed in larger series, mesothelin or MPF could be used as an adjunct to radiological monitoring in patients with epithelioid or mixed MM [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies (8)(9)(10)(11)(12)(13)(14) confirmed that serum SMRP was a promising marker for diagnosis, prognosis and clinical monitoring of MPM. High SMRP concentrations were detected in all the studies only in the epithelioid and mixed MPM.…”
Section: Soluble Mesothelin-related Peptides (Smrp)mentioning
confidence: 88%